Synergistic Toughening and Strain Releasing Strategy in Metal Halide Perovskite Photovoltaics - Wang, Chenyun; Shang, Chuanzhen; Feng, Haoyang; Lei, Yudong; Qu, Duo; Zhou, Bin; Zhang, Xinyue; Hu, Hanwei; Zhang, Yajie; Zhang, Zhanfei; Li, Bin; Bao, Zheng; et al. (Advanced functional materials, 2024)
Metal halide perovskite with high Young's modulus is prone to form cracks when subjected to mechanical stresses such as bending, twisting, or impacting, ultimately leading to a permanent decline in the performance of their photovoltaic devices. These mechanical properties pose challenges to the durability of long‐term service of photovoltaic devices and the production of flexible devices. To address this issue, the poly (lipoic acid‐co‐Styrene) elastomer is employed to modulate the modulus of perovskite films. The peak force quantitative nanomechanical atomic force microscopy measurements and nanoindentation tests demonstrated a reduction in modulus, with the lower modulus preventing the formation of cracks and defects during deformation. Moreover, this approach also suppressed the non‐radiative recombination of perovskite solar cells by leveraging the interaction between functional groups and defects. Through this method, the rigid inverted devices attained a power conversion efficiency of 24.42% alongside remarkable stability. Concurrently, flexible inverted devices achieved a power conversion efficiency of 22.21%. This strategy offers a promising avenue for fabricating flexible perovskite solar cells and enhancing their mechanical durability. Metal halide perovskites with high Young's modulus are prone to cracking under mechanical stress, which degrades device performance and durability. It is addressed by incorporating poly (lipoic acid‐co‐styrene) elastomer to lower the perovskite film's modulus. This strategy prevents cracks, reduces nonradiative recombination losses, and enhances power conversion efficiency.